An easy access to carboxylic acids via Pd-catalyzed hydrocarboxylation of olefins with HCOOLi as a CO surrogate under mild conditions. Issue 9 (26th July 2016) - Wang, Yang; Zeng, Yongming; Yang, Bangyu; Shi, Yian
Abstract : This paper describes an easy access to carboxylic acids via Pd-catalyzed hydrocarboxylation of olefins with HCOOLi and Ac2 O under mild conditions without using external CO gas. Abstract : This paper describes an easy access to carboxylic acids via Pd-catalyzed hydrocarboxylation of olefins with HCOOLi and Ac2 O under mild conditions without using external CO gas.